Evaluation of Traumatic Head Injury with neurological deficit (Article Review) - Al Dahhan, Musaed hekmat (International Journal of Psychosocial Rehabilitation, 2018)
Severe brain injury involves impaired autoregulation and responses in the injured brain through many mechanisms that lead to secondary brain injuries. Arterial hypotension, hypertension, or excess hyperventilation intended to reduce ICP in patients with damaged autoregulation response also lead to secondary brain injury and critical brain conditions after TBI that are associated with a poor outcome. The central dysregulation mechanisms after brain injury could contribute to the development and progression of extracerebral organ dysfunction by promoting systemic inflammation that may cause medical complications. Neurocritical care after severe TBI has therefore been refined to focus not only on secondary brain injury but also on systemic organ damage after excitation of sympathetic nerves following stress reactions.